(untitled) (Bangladesh Journal of Botany, 2020)
An experiment was conducted to evaluate the responses of various concentrations of NAA (25, 50, 75 ppm) and Pseudomonas inoculum on growth, yield and some biochemical parameters of sesame (Sesamum indicum L. var. BARI Til-4). Results revealed that application of NAA treatments and Pseudomonas inoculum reduced plant height non-significantly. Significant result was recorded on number of branches per plants from 50 ppm NAA treated plants. Plants treated with 75 ppm NAA produced maximum number of leaves, fresh and dry weight of leaves and roots, leaf area per plant and specific leaf weight whereas significant variation was found on leaf area. Seeds treated with Pseudomonas inoculum exhibited maximum shoot and root ratio which showed non-significant variation with the results of NAA treated plants. Yield contributing parameters viz., number of pods per plant, fresh and dry weight of pods per plant, 1000-seed weight were recorded maximum from 75 ppm NAA which were statistically similar to control. Maximum length of pod and number of seeds per pod were also recorded from 75 ppm NAA treated plants which eventually produced 32.54% higher yield than control. Harvest index was significantly influenced by all the treatments. Foliar NAA treatments and Pseudomonas inoculum had stimulatory effects on pigment contents of fresh leaves at vegetative stage where, Pseudomonas inoculum treated plants produced significantly higher chlorophyll a and carotenoids content than control. Significantly higher protein content of fresh leaves and seeds were also recorded from 75 ppm NAA treated plants. Out of four treatments, 75 ppm NAA produced better responses in most of the parameters.